2017
DOI: 10.1007/s11846-017-0246-z
|View full text |Cite
|
Sign up to set email alerts
|

Did UEFA’s financial fair play harm competition in European football leagues?

Abstract: When introducing UEFA's Financial Fair Play (FFP) it was argued that as a beneficial side effect competition in European football leagues should become more equilibrated and perceived as being fairer. Based on a hand-collected dataset on league results, player market values as well as investor payments of more than 300 European football clubs, we scrutinize the impact of FFP on the competitive landscape in major European football leagues. By applying a fixed-effect panel regression difference-in-differences ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 13 publications
1
26
0
6
Order By: Relevance
“…There is also emerging empirical literature on FFP and especially its effects on competitive balance. Birkhäuser et al (2019) examine league results, player market values, and investor payments relating to more than 300 European football clubs. The study's results are consistent with the view that FFP might have further amplified the competitive imbalance by reducing the equilibrium in European football leagues and freezing current hierarchies.…”
Section: Financial Fair Play Regulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also emerging empirical literature on FFP and especially its effects on competitive balance. Birkhäuser et al (2019) examine league results, player market values, and investor payments relating to more than 300 European football clubs. The study's results are consistent with the view that FFP might have further amplified the competitive imbalance by reducing the equilibrium in European football leagues and freezing current hierarchies.…”
Section: Financial Fair Play Regulationsmentioning
confidence: 99%
“…There are both theoretical (Franck, 2014;Peeters & Szymanski, 2014;Sass, 2016) and empirical analyses of UEFA's FFP, especially on its effects on competitive balance (Birkhäuser et al, 2019;Freestone & Manoli, 2017;Plumley, Ramchandani, & Wilson, 2019). Recent studies have found that the FFP has further amplified the competitive imbalance, but the effect is not uniform across leagues.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, several studies were conducted on competitive balance (CB) in the big five [5,[27][28][29], and CB was frequently emphasized as a key parameter for the sustainability of team sports leagues [30][31][32][33][34][35][36]. But CB does not look at the sustainability of the sporting competition or its structure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…La littérature sur les objectifs et l'efficacité du fair-play financier est aujourd'hui abondante (Barajas et al, 2017;Birkhäuser et al, 2019;Franck, 2018;Mareque et al, 2018;Plumley et al, 2018). Il ne nous est donc pas possible d'exposer ici l'ensemble des débats suscités par ce dispositif.…”
Section: Les Régulations Externesunclassified